DOUBLE-CHANNEL ELECTRODES - BEYOND THE LEVEQUE APPROXIMATION - Compton, R; Stearn, G (1988)
The theory of collection-efficiency measurements (under steady-state conditions) at double-channel electrodes has been extended to include practical conditions outside the range in which the Lévêque approximation can be reasonably invoked. The problem has been treated numerically using the backwards implicit finite difference method and the results compared with those obtained using existing analytical theory. The predicted behaviour of collection efficiency over a wide range of flow rates is supported by experimental data obtained using the reversible [Fe(CN)6]3-/[Fe(CN)6]4- system. The theory has been applied to the calculation of collection efficiency as a function of electrode potential for both reversible and irreversible electron transfers. It has also been employed to examine how the collection efficiency is affected when the electrode reaction produces a species with a diffusion coefficient greatly different from that of the starting material.